In vitro α-glucosidase inhibitory activity of Mahkota Dewa fruit flesh using different extraction methods - Abdur Rashid, Mohammad; Sarker, Md. Zaidul Islam; Ahmed, Qamar Uddin; Ferdosh, Sahena; Helal Uddin, A.B.M. (2021)
Purpose: Before using any plant for medicinal purposes, the proper extraction method must be considered for the bioactive compounds, which can be either polar or non-polar or both, and its advantages and disadvantages, depending on the selection process. The aim of this research was to compare the α-glucosidase inhibitory activity of Mahkota dewa fruit flesh using conventional and non-conventional extraction techniques.